ISTIHSAN DAN PEMBAHARUAN HUKUM ISLAM - Syarifuddin Syarifuddin (IAIN Ambon, 2017)
Islamic law is universal, elastic and dynamic. This concept provides implementable consequences for Muslims which able to prove and raise the Islamic values in the reality of life without crossing from their Islamic region, but also do not make silly attitudes that put Muslims in position lost to the outskirts of the cultural heritage area. Therefore, Prophet Muhammad SAW. has recommended and legitimized to his friend, Muadz bin Jabal for doing individual interpretation (ijtihad) in any settlement of problem which not found in al-Qor’an and Hadith. Furthermore, this raise a form of legal istinbat method is known as istihsan in Usul al-Fiqh. Nevertheless, the existence of istihsan is debated by the Islamic jurists. Key words: Istihsan, renewal, Islamic law